2023
DOI: 10.1088/1755-1315/1110/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Using Random Forest and Random Tree model to Predict the splitting tensile strength for the concrete with basalt fiber reinforced concrete

Abstract: The best model for predicting concrete splitting tensile strength using Basalt Fiber Reinforced Concrete (BFRC) was found utilising Random Forest (RF) and Random Tree (RT) implemented in this study. A total of 74 datasets were collected for this investigation from various academic papers. The entire data set is split into 51 training data sets and 23 testing data sets. The software which used for analysis in WEKA software. Cement, fine aggregate/crushed sand, coarse aggregate, water, superplasticizer, fly ash,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Zhang et al [46] also predicted the mechanical properties of composite laminate using a random forest model, and the results showed that the model was able to arrive at an accurate prediction in a shorter time. Similarly, researchers have used random forest regression to predict the mechanical properties of composites [13,47].…”
Section: Decision Treementioning
confidence: 99%
“…Zhang et al [46] also predicted the mechanical properties of composite laminate using a random forest model, and the results showed that the model was able to arrive at an accurate prediction in a shorter time. Similarly, researchers have used random forest regression to predict the mechanical properties of composites [13,47].…”
Section: Decision Treementioning
confidence: 99%
“…According to statistical metrics, LSTM-CHOA outperformed the other three models in predicting the kerf quality characteristics of cut composites. Almohammed and Soni [ 57 ] used Random Forest (RF) and Random Tree (RT) for predicting concrete splitting tensile strength using basalt fiber-reinforced concrete. Random Forest showed the best accuracy for predicting the splitting tensile strength according to performance metrics.…”
Section: Introductionmentioning
confidence: 99%